Invisibilidade, silêncios e angústia: o suicídio de jovens LGBTQIA+ e o embate entre família, religiosidade e o desejo e direito de ser e pertencer. - Santos, Jacquelane Bezerra dos (2024)
The growing number of cases of religious intolerance and LGBTphobia on social media, led by religious leaders and their hate speech, has contributed directly or indirectly to the increase in cases of mental disorders, such as anxiety and depression, resulting in cases of suicide among teenagers and young people. LGBTQIA+. Hermetic and cruel positions exposed in LGBTphobic speeches given on the internet by religious leaders who endorse situations of great suffering for non-heteronormative people and groups; instigating people who belong to fundamentalist families to oppress their loved ones within their homes, drunk by an exclusionary, prejudiced and distorted vision of the good news of the practice of love, recommended by Jesus Christ, in the midst of social confinement as a result of health standards for control Covid-19 pandemic, and overwhelmed by hate speech on social media, gained exorbitant followers, who share the same stance. This toxicity has had a great impact on the increase in Christian religious fundamentalisms that demonize and reject everything that is contrary to their dogmas, increasing the mental suffering of those they subjugate and mediocriizing the aggregating stance that religious institutions should have, in environments of subjugation of the be deviant. The present study leads us to reflect on how Brazil achieved the title of country with the highest levels of anxiety in the world; at the same time that, according to the latest IBGE census, we have a country with a greater number of churches than schools. In the same vein, Brazil is going against the grain of the world with the increase in the number of suicide cases among adolescents and young people, and, for the 14th time in a row, it leads the ranking of countries that take the most lives of LGBTQIA+ people around the world. It is necessary to state that none of this is a mere coincidence. The internet provided a favorable environment to expand hate speech from conservative and fundamentalist positions in families, under the Nazi motto of “God, country and family”, unifying three of the main social institutions, equipping ideologies, rejecting diversities and differences such as part of a project to perpetuate power. Even in an adverse scenario, there is resistance, mobilizations of collectives for diversity. A significant part of civil society, especially progressive churches, remains firm in the fight to guarantee the existence and survival of plurality, respect and love, echoing the saying in the composition by Milton Nascimento and Caetano Veloso: “any form of love is worth Too bad, any form of love is worth loving. ”